DINAMIKA TANDA DALAM REBRANDING TIKTOK : ANALISIS SEMIOTIKA ROLAND BARTHES PADA EVOLUSI LOGO MUSIK - Nurhafiza Yusro; Nadia Sun Sanjayani (ADISAM PUBLISHER, 2025)
This study examines the evolution of the TikTok music logo using Roland Barthes' semiotic analysis to understand the dynamics of signs in the platform's rebranding process. Using a qualitative approach, this study analyses primary data in the form of three versions of the TikTok music logo (2016-2018, 2019-2021, 2022-present) and secondary data from official TikTok documentation, media reviews, and user responses. The results show that the evolution of the TikTok music logo represents three phases of meaning transformation: from a simple initial identity (2016-2018), to a more dynamic transition phase (2019-2021), to a sophisticated minimalist design (2022-present). Semiotics analysis reveals a shift in meaning from the level of denotation (physical change of the logo), connotation (transformation of the platform's identity), to myth (TikTok as a pioneer of digital innovation). The study also found that visual changes correlate positively with a 45% increase in brand trust among Gen Z users